2021
DOI: 10.3389/fgene.2020.581993
|View full text |Cite
|
Sign up to set email alerts
|

Integration of Transcriptional and Post-transcriptional Analysis Revealed the Early Response Mechanism of Sugarcane to Cold Stress

Abstract: Cold stress causes major losses to sugarcane production, yet the precise molecular mechanisms that cause losses due to cold stress are not well-understood. To survey miRNAs and genes involved in cold tolerance, RNA-seq, miRNA-seq, and integration analyses were performed on Saccharum spontaneum. Results showed that a total of 118,015 genes and 6,034 of these differentially expressed genes (DEGs) were screened. Protein–protein interaction (PPI) analyses revealed that ABA signaling via protein phosphatase 2Cs was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 61 publications
0
3
0
Order By: Relevance
“…The transcriptome data of different sugarcane tissues, including bud, leaf, epidermis, stem pith, and root from ten-month-old sugarcane cultivar ROC22, were derived from the transcriptome of our group (unpublished). The transcriptome data of different sugarcane cultivars under the stress of S. scitamineum were obtained from Que et al [71], and the materials were selected from ROC22 (susceptible cultivar) and Yacheng 05-159 (YC05-159, resistant cultivar) with the bud samples infected by S. scitamineum for 0, 1, 2, and 5 d. The cold stress transcriptome data (PRJNA636260) were obtained from Huang et al [72], and the selected material was GX87-16 cultivar, which was treated at low temperature two weeks after pot planting, and the leaf samples of 0, 0.5, 1, and 6 h after treatment were taken. The drought stress transcriptome data (PRJNA590595) of Co 06022 (susceptible cultivar) and Co 8021 (resistant cultivar) were obtained from Selvi et al [73].…”
Section: Transcriptome Data Analysismentioning
confidence: 99%
“…The transcriptome data of different sugarcane tissues, including bud, leaf, epidermis, stem pith, and root from ten-month-old sugarcane cultivar ROC22, were derived from the transcriptome of our group (unpublished). The transcriptome data of different sugarcane cultivars under the stress of S. scitamineum were obtained from Que et al [71], and the materials were selected from ROC22 (susceptible cultivar) and Yacheng 05-159 (YC05-159, resistant cultivar) with the bud samples infected by S. scitamineum for 0, 1, 2, and 5 d. The cold stress transcriptome data (PRJNA636260) were obtained from Huang et al [72], and the selected material was GX87-16 cultivar, which was treated at low temperature two weeks after pot planting, and the leaf samples of 0, 0.5, 1, and 6 h after treatment were taken. The drought stress transcriptome data (PRJNA590595) of Co 06022 (susceptible cultivar) and Co 8021 (resistant cultivar) were obtained from Selvi et al [73].…”
Section: Transcriptome Data Analysismentioning
confidence: 99%
“…In addition, cold stress leads to increased peroxidation of the leaf membrane, and increased soluble sugar, proline, and MDA content, but decreased chlorophyll content in sugarcane [ 28 , 29 ]. At a molecular level, studies revealed that cold stress influenced the expression of several genes in sugarcane, including those identified by bioinformatic analyses to be involved in calcium metabolism [ 30 , 31 ]. Similar results were reported in other plant species [ 32 , 33 , 34 ].…”
Section: Discussionmentioning
confidence: 99%
“…Overexpressed OsmiR528 cell lines improve lowtemperature tolerance and stress response transcription factors. A distinct group of miRNAs, including miR444, miR169, and miR396, increases lignin metabolism, transcription, and signal transduction in sugarcane via regulating cold stress [147]. The structural characteristics of miRNA and TF revealed that the interaction of miRNA and transcription factors governs multiple gene expression, which aids in cellular protection against various abiotic stresses[148].…”
Section: Tf-mirna Interaction In Plant Response Towards Cold Stress A...mentioning
confidence: 99%